Effectiveness of deep dry needling versus manual therapy in the treatment of myofascial temporomandibular disorders: a systematic review and network meta-analysis - Ángela Menéndez-Torre; Aitor Martín Pintado-Zugasti; Juan Nicolás Cuenca Zaldivar; Paula García-Bermejo; Diego Gómez-Costa; Miguel Molina-Álvarez; Alberto Arribas-Romano; Josué Fernández-Carnero (Chiropractic & Manual Therapies, 2023)
Abstract Background Temporomandibular disorders (TMDs) are the most common cause of orofacial pain of non-dental origin, with approximately 42% of diagnoses corresponding to myofascial pain. Manual therapy and dry needling are commonly used interventions for the treatment of myofascial temporomandibular disorders. However, it is unclear whether one of them could be superior to the other. Objectives The aim of the present systematic review and network meta-analysis was to compare the effectiveness of manual therapy and dry needling in patients with myofascial TMD. Methods This is a systematic review and network meta-analysis. Randomized clinical trials were searched in the databases of Pubmed, PEDro, CINAHL, Web of Science, Scopus, Cochrane, Google Academic and EMBASE. The methodological quality of studies included in this review was judged using the Physiotherapy Evidence Database (PEDro) scale. A frequentist network meta-analysis was carried out, assuming random effects, to estimate the effects of interventions for temporomandibular joint pain measured on a 10-point visual analogue scale. Results Out of 3190 records identified, 17 met the inclusion criteria for qualitative analysis and eight were included in the network meta-analysis. Indirect comparisons between dry needling and manual therapy showed no significant differences in their effects on pain reduction (Odds Ratio [95%CI]; − 0.263 [− 1.517, 0.992]). The ranking of treatments shows that manual therapy (SUCRA = 0.932) followed by deep dry needling (SUCRA = 0.775) present the highest values of estimation and can be considered the most likely to reduce pain. Conclusions The results of the network meta-analysis should be considered with caution due to the low quality of the evidence available and the high variability of the study protocols in terms of the method of application of dry needling and manual therapy interventions. PROSPERO under identifier: (CRD42020186470).